Cavernous Sinus Thrombosis focusing on odontogenic causes: a narrative review - Almeida, Ana Carolina Plado Barreto de; Coelho, Andressa da Silva; Castro, Daniel Pereira de Faria; Sperandio, Davi Marcos da Silva; Segal, Igor Cukierman; Prado, Roberto (Journal of Oral Diagnosis, 2022)
Cavernous Sinus Thrombosis (CST) is an uncommon neurological infection that affects the cavernous sinus of the dura mater, which can lead to death. When untreated, odontogenic infections can cause CST, since facial veins do not have valves. The diagnosis consists of the clinical characteristics added to imaging exams such as computed tomography (CT) and magnetic resonance imaging (MRI). The effectiveness of antibiotic therapy in significantly reducing mortality has been proven, but therapy with anticoagulants and corticosteroids remains unknown in the literature. Objective: The purpose of the study is to make a literature review on etiology, paraphysiology, symptoms, complementary exa- ms, diagnosis and outcome of patients who presented CST as a result of an odontogenic infection. Materials and methods: a literature review was carried out, using articles from the Pubmed, Lilacs and Cochrane databases, from the last 10 years in the English langua- ge and reference articles to complement. The Mesh terms used were ‘Cavernous Sinus Thrombosis’, ‘Cavernous Sinus Thrombosis AND Odontogenic Infections’ and ‘Cavernous Sinus Thrombosis AND Dental Infection’. Conclusion: CST motivated by odontogenic infections is a rare but extremely dangerous disorder that must be discovered early in order for the patient’s prognosis to be favorable. It is necessary to pay attention to the clinical signs and to the analysis of the imaging exams so that the differential diagnosis is made.